Tratamento orto-cirúrgico para correção de deformidade dentomucoesquelética - Corrêa, Márcio Aurélio (2014)
In the majority of cases, the patient's rehabilitation involves multidisciplinary treatment, seeking therapies with the goal of restoring compromised esthetics and function. Esthetics involve not only the teeth or esthetic harmony of the face, based on a good relationship of the bony bases, but it is relevant to reconstitute the bone and gingival tissues - this set being primordial for the success of the treatment to which the patient is submitted. The aim of this study was to relate, by means of a clinical case report, the importance of multidisciplinary treatment and correct diagnosis to make it possible to direct the treatment of buccofacial and dentofacial deformities. The clinical case reports the patient's condition with regard to maxillary bone deficiency, generating a Class III maxillomandibular discrepancy, loss of bone structure in the pre-maxillary region, compromising esthetics and the peri-implant tissues in the region of teeth 11 and 21. Various treatment alternatives were discussed, however, the treatment that was approved by the team and accepted by the patient involved the following procedures: Orthodontic decompensation treatment, with a view to performing orthognathic surgery; removal of the implants of teeth 11 and 21 and migration of teeth 12 and 22 (condemned, with severe bone defect in the mesial wall), and later extrusion of these teeth with the purpose of creating bone in order to place implants in the region without the need for grafts. It was concluded that knowledge of the patient's chief complaint and expectations, well performed diagnostic exams allied with integrated planning were primordial in the decision about the treatment plan and success of the final result.